Observation of top quark production in proton-nucleus collisions - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Brandstetter, Johannes; Md. Ali, Mohd. Adli (American Physical Society, 2017)
The first observation of top quark production in proton-nucleus collisions is reported using proton-lead data collected by the CMS experiment at the CERN LHC at a nucleon-nucleon center-of-mass energy of sNN=8.16 TeV. The measurement is performed using events with exactly one isolated electron or muon candidate and at least four jets. The data sample corresponds to an integrated luminosity of 174 nb-1. The significance of the tt signal against the background-only hypothesis is above 5 standard deviations. The measured cross section is σtt=45±8 nb, consistent with predictions from perturbative quantum chromodynamics.